Transfers, nutrition programming, and economic well-being: Experimental evidence from Bangladesh - Ahmed, Akhter; Hoddinott, John F.; Roy, Shalini; Sraboni, Esha (International Food Policy Research Institute, 2019)
Interest has grown in leveraging cash transfer programs with nutrition interventions to improve child nutrition at scale. However, little is known about how doing so affects household economic well-being. We study a program providing cash or food transfers, with or without nutrition behavior change communication (BCC), to poor women in rural Bangladesh. We find that adding BCC to cash or food transfers leads to larger impacts on both consumption and assets - an apparent puzzle, given the transfer value is unchanged. Evidence suggests this occurs through the BCC inducing increases in income generation - plausibly by improving households’ social capital and empowerment.